Numerical Simulation of Flow-Induced Vibration of Three-Dimensional Elastic Heat Exchanger Tube Bundle Based on Fluid-Structure Coupling - Shiqin Ai; Chao Sun; Yuechan Liu; Yuelin Li (Shock and Vibration)
The reliability of the heat exchanger tube bundle not only affects the economic efficiency of production but also relates to the normal development of production safety and health. To study the flow-induced vibration of tube bundles, a three-dimensional finite element model of heat exchange tubes and watersheds inside and outside the tubes was established to explore the flow-induced vibration characteristics of tube bundles and analyze the natural frequencies of single-span and multispan heat exchange tubes. Considering the randomness of the effective support between the tube bundle and the support plate of the heat exchanger, the natural frequency and vibration mode of the four-span tube with failure of the tube bundle support are analyzed. On this basis, the vibration caused by the two-way coupling flow between tube and tube outflow is calculated. Finally, the flow-induced vibration characteristics of the five-tube bundle with two different pitch-diameter ratios are analyzed. The calculation results show that the error between the calculated natural frequencies and the theoretical values is less than 3%, and within the allowable error range, the natural frequencies of the same order decrease with the increase of the number of support failures. The vibration frequencies of single-span and multispan tube bundles are consistent with the lift and drag frequencies, the vibration displacement curves show typical Strouhal modes, and the amplitude increases with the increase of fluid velocity. Vibration displacement curves of symmetrical spans of multispan tube bundles are similar in shape and amplitude. With the increase of tube bundle spacing, the vibration characteristics become more obvious.